The Marketing Mix Factors Affecting Purchasing Decisions for Non-animals Testing Cosmetic and Skincare Products. - Thitiphada Khrueanugool, Paitoon Chetthamrongchai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study has an objective to examine the impact of marketing mix factors on purchasing decisions of non-animals testingcosmetic and skincare products on students and employees at HEG University, Switzerland. This research is descriptive causative research aims to find the influence of an independent variable that is in this research is product, price, promotion and distribution to dependent variable that is purchase decision. The number of samples is 68 respondents.Analytical technique used is mean and standard deviation. The study revealed that Product and Promotion were extremely important factors affecting consumer purchasing decision. And then Place about cosmetic retail stores and Price respectively. On the other hand, marketing factors that respondents gave the least importance is Product about packaging. The respondents gave neutral important at this point. For the content and motivation in communicating and convincing consumers of cosmetic companies and organizations that banned animals testing found that most respondents purchase cosmetic and skincare products once a month. They agreed that cosmetic and skincare companies that prohibit animal testing have a better image than the cosmetic and skincare company that used animals-testing. And also, it is not necessary to experiment on animals for cosmetic industry because nowadays there are many volunteers who willing to experiment and have the lab to grow artificial human skin for cosmetics and skincare testing. Moreover, non-animal test logo on cosmetic and skincare products were reliabilities and affecting the consumer purchasing decision. And most respondents tend to have intention to purchase cosmetic and skincare products that are non-animals testing.